Le tunumiisut, dialecte inuit du Groenland oriental - Mennecier, Philippe (HAL CCSD, 1994)
This study is a synchronic description of tunumiisut, an Inuit dialect spoken in the district of Ammassalik (east coast of Greenland). It is the first carried out since W. Thalbitzer's study of 1921 and is founded on a field-corpus collected between 1985 and 1991; it adopts a functional approach. Examples are taken from linguistic questionnaires and also from a spoken text presented using different levels of transcription. The test of frequency, both in lexis and in discourse, is widely used to complement phonological, syllabic analysis, and the study of phonemic combinations and of word classes. Special attention is given to phonetic realisations in discourse, and to the treatment of loan words. The morphophonological phenomena, which are complex in all Inuit dialects, are analysed in detail. Word classes are defined according to their combinatorial and collocational possibilities rather than according to semantic criteria. The question of verb-noun opposition and the question of verb classes are treated in detail. The classification of the numerous derivational affixes is based on morphosyntactic criteria. The function of so-called "ergative" and "antipassive" utterances is re-examined, as are the relations between the morphosyntactic constraints and the semantic constraints which determine their use. Cette description synchronique du tunumiisut, dialecte inuit parlé dans le district d'Ammassalik (côte orientale du Groenland), est la première depuis l'élude réalisée par W. Thalbitzer en 1921. Elle se fonde sur une analyse fonctionnaliste, faite à partir d'un corpus constitué sur le terrain, entre 1985 et 1992. Les exemples sont tirés de questionnaires d'enquête linguistique, mais aussi d'un récit présenté ici avec différents niveaux de transcription. Le critère de la fréquence, en lexique et en discours, est largement utilisé pour compléter l'analyse phonologique, celle des structures, des combinaisons de phonèmes et des classes de mots. On accorde une place particulière aux réalisations phonétiques en ...